Pengaruh Pemahaman Perpajakan, Tingkat Pendidikan, Tingkat Pendapatan Terhadap Kepatuhan Pendaftaran Nomor Pokok Wajib Pajak - Nia Audina; Afifudin Afifudin; Umi Nandiroh (Universitas Islam Malang, 2023)
Currently, almost many employers require their employees to have a NPWP to facilitate tax administration. Having a NPWP will make it easier for us to handle administrative requests like at a bank. Several banking institutions currently require the entry of a NPWP number as one of the main requirements or supporting documentation requirements in the administration process. The aim of this research is to determine the effect of understanding taxation, education level, income level on NPWP registration compliance at the Muhammadiyah University of Malang. The type and source of data used in this research is primary data, using quantitative data. Sampling in this study was carried out using the Slovin technique. Understanding of taxation, level of education, level of income have a significant effect on Taxpayer Identification Number Registration Compliance, obtaining an F value of 5.344 with a significant value of 0.002 which is smaller than 0.05.Keywords: understanding of taxation, education level, income level, NPWP registration compliance.